Crypt of the moon spider - Ballingrud, Nathan (Ballingrud, Nathan. Lunar gothic trilogy, 2024)
"Years ago, in a cave beneath the dense forests and streams on the surface of the moon, a gargantuan spider once lived. Its silk granted its first worshippers immense faculties of power and awe. It's now 1923 and Veronica Brinkley is touching down on the moon for her intake at the Barrowfield Home for Treatment of the Melancholy. A renowned facility, Dr. Barrington Cull's invasive and highly successful treatments have been lauded by many. And they're so simple! All it takes is a little spider silk in the amygdala, maybe a strand or two in the prefrontal cortex, and perhaps an inch in the hippocampus for near evisceration of those troublesome thoughts and ideas. But patients aren't the only ones with trouble on their minds, and although the spider's been dead for years, its denizens are not. Someone or something is up to no good, and Veronica just might be the cause"--